Generators of mammalian vestibular surface responses to head motion - Gaines, Gary Christopher (East Carolina University, 2012)
The linear vestibular sensory evoked potential (VsEP) is thought to be the compound electrical response of peripheral macular neurons and central neural relays, and as such used to directly assess macular function. The VsEP is used in animal research to study, among other things, the genetic basis of deafness and balance disorders. Although the neural generators of the linear VsEP have been described in the bird, the precise central neural generators have not been documented for the mouse model. Because the mouse is such a valuable model in vestibular research, it is important to clearly identify the peripheral and central generators of VsEPs in mice. In order to complete such studies, various preface studies were completed to insure the accuracy of measurement with the generator studies. These studies included evaluation of VsEP response morphology with change in brain temperature; evaluation of drug on the VsEP response (i.e., Ketorolac); and the evaluation of stimulus duration on the VsEP response. During generator studies, VsEPs before and after strategic surgical manipulations of vestibular pathways were recorded. This included isolation of the eighth nerve from central relays and destruction of   central candidate neural generators. The extent of lesions was characterized histologically and changes in response components were documented. Response components critically dependent on particular peripheral and central structures were identified. These studies have increased the understanding of the neural generators of the VsEP, and in turn, enhanced the ability to assess peripheral and central vestibular function and detect vestibular disease.
Keywords: Audiology; Neuroscience; Balance; Ear; NSAID; Vestibular; VsEP; Biology, Neuroscience; Vestibular Evoked Myogenic Potentials; Ketorolac; Mice; Investigative Techniques; Vestibule, Labyrinth--physiology; Reflex, Vestibulo-Ocular; Vestibular Nuclei--physiology; Evoked Potentials; Auditory Pathways; Auditory Pathways--physiology; Models, Animal